2013
DOI: 10.4067/s0717-95022013000200037
|View full text |Cite
|
Sign up to set email alerts
|

How Does Protein Malnutrition or Food Deprivation Interfere with the Growth of the Epiphyseal Plate in Animals?

Abstract: the aim of this study was to conduct a literature review of impacts of protein malnutrition and/or early food deprivation on the formation of the growth plate in young animals. A search was performed using the databases PubMed/MEDLINE, LILACS, SciELO and the Cochrane Library, without language restrictions or any limit as to year. Initially, 150 articles were identified, however, after application of the inclusion and exclusion criteria only five remained. In three studies the nutritional stress was due to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…With respect to growth, this may be threatened in young, still-growing athletes if energy availability is insufficient to meet the simultaneous demands of training, in addition to other essential maintenance functions, and growth. Research performed in rats and rabbits indicated negative impacts of nutritional deprivation on bone epiphyseal plates [110], with implications for longitudinal bone growth. Potential adverse effects of LEA on growth may be particularly relevant in sports that simultaneously emphasize early specialization and leanness and/or lightness (e.g., dancers, gymnastics, and horse-racing jockeys), given that athletes may be required to maintain low body mass at pivotal developmental stages.…”
Section: Growth and Immune Defencementioning
confidence: 99%
“…With respect to growth, this may be threatened in young, still-growing athletes if energy availability is insufficient to meet the simultaneous demands of training, in addition to other essential maintenance functions, and growth. Research performed in rats and rabbits indicated negative impacts of nutritional deprivation on bone epiphyseal plates [110], with implications for longitudinal bone growth. Potential adverse effects of LEA on growth may be particularly relevant in sports that simultaneously emphasize early specialization and leanness and/or lightness (e.g., dancers, gymnastics, and horse-racing jockeys), given that athletes may be required to maintain low body mass at pivotal developmental stages.…”
Section: Growth and Immune Defencementioning
confidence: 99%